EFFECT OF TRIS AND OVINE FREEZING SEMEN EXTENDERS ON CYTOPLASMATIC MEMBRANE INTEGRITY DURING OVINE SEMEN FREEZING IN 0.5 ML STRAWS - Cabrera V., Próspero (2008)
The effect of two semen extenders: Glucose Tris and Ovine Freezing Buffer (UA 466/ 005238) on the motility and cytoplasmic membrane integrity of spermatozoa during the freezing process was evaluated. Five rams (2 Assaf, 2 Cinnamon and 1 Black Belly) were used. The fresh semen was of good quality and values of seminal characteristics were within the normal range for this species. The Progressive Individual Motility of the refrigerated semen was 86.0 ± 2.48 and 88.5 ± 4.8% and for frozen semen was 60.8 ± 1.9 and 62.9 ± 2.4% for Tris and Ovine Freezing, respectively; while the proportion of spermatozoa with intact membranes, evaluated by HOST (Hipo Osmotic Swelling Test), was 77.9 ± 4.8 and 78.9 ± 4.0% for refrigerated semen and 39.9 ± 3.6 and 43.2 ± 2.9% for frozen semen using the Tris and Ovine Freezing dilutors, respectively. There were highly significant differences between dilutors, rams and phases of the freezing process (p<0.01). Significant lineal regressions (p<0.05) were found between HOST values of fresh semen and HOST values of thawed semen, either with Tris or Ovine Freezing. It can be concluded that the Ovine Freezing semen extender showed a better performance during the freezing process; moreover, the hypoosmotic test showed to be a good indicator tool for semen quality.